Validation of the Flemish version of the Quality of Life in Short Stature Youth (QoLISSY) questionnaire. Issue 3 (June 2014) - Rohenkohl, A. C.; De Schepper, J.; Vanderfaeillie, J.; Fricke, K.; Hendrickx, S.; Lagrou, K.; Bullinger, M.; Quitmann, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The Quality of Life in Short Stature Youth (QoLISSY) questionnaire was recently developed in five European countries to assess health-related quality of life in children and adolescents with idiopathic short stature or growth hormone deficiency from child and parent perspectives. In addition to the existing French version, a Flemish version is needed for use of QoLISSY in the Flemish speaking part of Belgium. Methods: Children (8–18 years) and their parents recruited from two Belgian paediatric endocrinology clinics completed the QoLISSY in a cross-sectional study. Cronbach's Alpha and test–retest reliability was assessed. Validity was examined by correlation with the generic KIDSCREEN questionnaire as well as by group comparisons according to diagnostic and treatment status. Results: The QoLISSY scales had an acceptable internal consistency with Cronbach's Alpha ranging from 0·80 to 0·94 (child version) and from 0·77 to 0·92 (parent version). Test–retest reliability correlation coefficients ranged from r = 0·75 to 0·89 in the child version and from r = 0·58 to 0·85 in the parent version. Moderate correlations with the generic KIDSCREEN questionnaire suggested construct validity. Differences between child groups according to child age, underlying diagnosis, and degree of height deficit were found. Correlations with the European QoLISSY were significant for all scales. Discussion: The Flemish QoLISSY instrument is a psychometrically sound, reliable, and valid short stature specific questionnaire measuring health-related quality of life. It is expected to be of great use in upcoming clinical research on growth disorders and growth hormone treatment in Belgium and Europe.